CHOPPED-POT SITUATION IN TEACHERS DEVELOPMENT VIA ACTION RESEARCH TECHNIQUES IN CYBER ERA - Kropáč, Jiří (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Chopped-pot (chop pot) is a poker term and a critical opening metaphor for this article. Applied action research steps and these extensions are necessary for practice during a pandemical situation in unstable and challenging teaching at universities in Czechia. Forms of teaching, personal contact and process of monitoring students’ results have changed dynamically. Mass influence of pandemic situation stopped actions at schools and many institutions all over the world. In Czechia, there has been transferred all practical and cognitive (theoretical) subjects to cyberspace. Due to the lack of government information, public fear and low digital literacy level, students have been learning in virtual classes and individual consultations. Many of them have lost contact with their critical practice and opportunities to transfer their knowledge into the school environment. We tried to modify classical action research approaches to new conditions in cyberspace and use it for pre-service and teachers’ innovation from an innovative perspective. In the methodological part, there is research presented from a full semester of gradual teachers’ development. The constructed research tool was tested in virtual conditions and monitored activities and the progress of development in teachers’ self-reflection for their future daily practice. The mixed design of research tools and a combination of the postproduction process of data open scientific feedback for their subjective inquiries in the individual personal development of educational staff in Czechia via action research model.